High Job Demands and Low Job Control Increase Nurses' Professional Leaving Intentions: The Role of Care Setting and Profit Orientation. Issue 5 (25th May 2016) - Wendsche, Johannes; Hacker, Winfried; Wegge, Jürgen; Rudolf, Matthias
Abstract: We investigated how two types of care setting (home care and nursing home) and type of ownership (for‐profit vs. public/non‐profit) of geriatric care services interacted in influencing registered nurses' intention to give up their profession. In prior research, employment in for‐profit‐organizations, high job demands, and low job control were important antecedents of nurses' intent to leave. However, the impact of care setting on these associations was inconclusive. Therefore, we tested a mediated moderation model predicting that adverse work characteristics would drive professional leaving intentions, particularly in for‐profit services and in nursing homes. A representative German sample of 304 registered nurses working in 78 different teams participated in our cross‐sectional study. As predicted, lower job control and higher job demands were associated with higher professional leaving intentions, and nurses reported higher job demands in public/non‐profit care than in for‐profit care, and in nursing homes compared to home care. Overall, RNs in nursing homes and home care reported similar intent to leave, but in for‐profit settings only, nurses working in nursing homes reported higher professional leaving intentions than did nurses in home care, which was linked to lower job control in the for‐profit nursing home setting, supporting mediated moderation. Taken together, our results indicate that the interplay of care setting and type of ownership is important when explaining nurses' intentions to give up their profession. © 2016 Wiley Periodicals, Inc.